Porous carbon material, silicon carbon material, secondary battery, and electric device

By designing porous carbon materials with suitable porous structure and particle size distribution, the problem of poor circulation performance of secondary batteries in the prior art is solved, and a higher number of cycles and more stable battery performance is achieved.

CN119833587APending Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202410302250.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-15
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing porous carbon materials have poor circulation performance in secondary batteries, which affects the high energy density and stability of the battery.

Method used

A porous carbon material is designed, which includes mesoporous and micropores, the number of mesoporous pores is not less than the number of micropores, the volume distribution particle size of carbon particles is in the range of 0.5 μm to 1.0 μm, and the specific surface area is between 1400 m2/g and 1800 m2/g. This material increases the number of cycles of the battery by reducing the circulation expansion of the silicon material.

Benefits of technology

The cycle performance of the battery is improved, the cycle number of the battery is increased, and the probability of side reactions is reduced while maintaining high first-term efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833587A_ABST
    Figure CN119833587A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a porous carbon material, a silicon carbon material, a secondary battery and an electric device. The porous carbon material comprises carbon particles, the carbon particles have a porous structure, the porous structure comprises mesopores and micropores, and the number of the mesopores is not less than that of the micropores; the volume distribution particle size of the carbon particles meets the condition that Dv1 is greater than or equal to 0.5 mu m, and the specific surface area of the porous carbon material is 1,400 m < 2 > / g to 1,800 m < 2 > / g. The porous carbon material provided by the invention has a suitable porous structure, the number of micropores and mesopores in the porous structure is controllable, the content of a silicon material formed in the porous structure and the size of silicon crystal grains can be conveniently controlled, and a part of volume space for buffering the expansion of the silicon material can be reserved to improve the cyclicity of a battery; on the other hand, micro-powder particles attached to the surfaces of the carbon particles are reduced, the volume distribution particle size concentration ratio of the carbon particles is improved, and the number of cycles of the battery is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a porous carbon material, a silicon-carbon material, a secondary battery and an electrical device. Background Art

[0002] Porous carbon material is a carbon material with a network structure consisting of interconnected or closed pores, which has strong adsorption properties. It can be used to deposit silicon materials to improve the high energy density of secondary batteries while alleviating a certain degree of expansion of silicon materials. However, the porous carbon materials currently used are still not ideal and are more likely to affect the cycle performance of secondary batteries, limiting the further development of battery technology. Summary of the invention

[0003] In view of the above problems, the present application provides a porous carbon material, a silicon-carbon material, a secondary battery and an electrical device, which are beneficial to improving the performance of the battery. For example, while maintaining the material with a relatively high initial efficiency, the cycle expansion capacity is reduced to increase the number of battery cycles, thereby improving the cycle performance of the battery.

[0004] The first aspect of the present application is to provide a porous carbon material, wherein the porous carbon material comprises carbon particles, wherein the carbon particles have a porous structure, and the porous carbon material satisfies the following conditions:

[0005] (1.1) The porous structure contains mesopores and micropores, and the number of mesopores is not less than that of micropores;

[0006] (1.2) The volume distribution particle size of the carbon particles satisfies: Dv1 ≥ 0.5 μm;

[0007] (1.3) The specific surface area of ​​porous carbon material is 1400 m 2 / g~1800m 2 / g.

[0008] The porous carbon material provided in the present application has a suitable porous structure, in which the number of mesopores is not less than the number of micropores, because generally speaking, the pore size of the micropores is smaller than the pore size of the mesopores, wherein the micropores are mainly used to facilitate the subsequent deposition of silicon materials, and on the basis of improving the capacity of the porous carbon material, the amount of silicon material deposited can be limited to reduce the effect of the expansion of the silicon material on the porous carbon material structure, thereby affecting the cyclicity of the battery. The mesopores are mainly used to facilitate the volume expansion of the slow-release porous carbon material. When the number of mesopores is greater than or equal to the number of micropores, it can not only limit the expansion degree of the silicon material itself, but also provide sufficient slow-release space for the expansion of the silicon material. On the other hand, by controlling the number of micropores and mesopores in the porous structure to form a porous carbon material with a relatively high specific surface area, the specific surface area of ​​the porous carbon material is larger than that of conventional materials, and the beneficial effects brought by it include: facilitating the subsequent deposition of silicon materials, and conveniently controlling the silicon material content and silicon grain size formed in the porous structure, and also reserving part of the volume space for buffering the expansion of the silicon material. In addition, conventional carbon particles contain small-sized micropowder particles, such as micropowder particles with a particle size of less than 0.5 μm. These micropowder particles are easy to adhere to the surface of carbon particles during the subsequent formation of silicon materials, which directly increases the probability of side reactions between silicon-carbon materials and electrolytes. This application removes small-sized micropowder particles and controls the particle size of carbon particles to reduce the impact of side reactions on battery cycle performance. Therefore, the porous carbon material designed in this application improves the battery cycle performance by reducing cycle expansion while maintaining a relatively high initial efficiency of the material to increase the number of battery cycles.

[0009] In some embodiments of the present application, the volume distribution particle size of the carbon particles satisfies: Dv1 is 0.5 μm to 1.0 μm.

[0010] In some embodiments of the present application, the volume distribution particle size DV of the carbon particles is 50 、DV 90 With DV 10 Satisfy the following:

[0011] DV 50 3μm~20μm;DV 90 ≤35μm; DV 10 >1.5μm.

[0012] In some embodiments of the present application, the volume distribution particle size DV of the carbon particles is 50 5μm~19μm.

[0013] In some embodiments of the present application, the specific surface area of ​​the porous carbon material is 1450 m 2 / g~1750m 2 / g.

[0014] In some embodiments of the present application, the porous structure satisfies the following conditions:

[0015] (2.1) The number of mesopores accounts for more than 50% of the number of porous structures;

[0016] (2.2) The number of micropores accounts for less than 50% of the number of porous structures;

[0017] (2.3) The average pore size of the porous structure is 1.0 nm to 10 nm.

[0018] In some embodiments of the present application, the porous structure satisfies at least one of the following:

[0019] (3.1) The number of mesopores accounts for 50% to 70% of the number of porous structures;

[0020] (3.2) The number of micropores accounts for 30% to 50% of the number of porous structures;

[0021] (3.3) The average pore size of the porous structure is 2.0 nm to 8.0 nm.

[0022] In some embodiments of the present application, the pore volume of the porous carbon material is 0.8 cm 3 / g~1.4cm 3 / g.

[0023] The second aspect of the present application is to provide a silicon-carbon material, which includes the porous carbon material disclosed in the first aspect, and also includes silicon grains and a carbon coating layer, wherein the silicon grains are formed in the porous structure; and the carbon coating layer is located outside the porous carbon material.

[0024] In the silicon-carbon material provided by the present application, silicon grains are mainly formed in the micropores of the porous carbon material to facilitate the control of the specific content, and most of the reserved mesopores are mainly used as volume space to buffer the expansion of the silicon material. The carbon coating layer as an outer shell layer can reduce the probability of silicon grains contacting with the outside air and then being oxidized, and can reduce the probability of silicon grains contacting and reacting with the electrolyte. Therefore, the silicon-carbon material designed in this application improves the cycle performance of the battery by reducing the cycle expansion while maintaining the relatively high initial efficiency of the material. .

[0025] In some embodiments of the present application, the silicon-carbon material contains silicon element, and the mass percentage content of the silicon element is 30% to 40%, preferably 35% to 40%, based on the total mass of the silicon-carbon material.

[0026] In some embodiments of the present application, silicon grains are formed in the micropores of the porous structure;

[0027] Preferably, the grain size of the silicon grains is ≤8.0 nm, preferably 5.0 nm to 8.0 nm.

[0028] In some embodiments of the present application, the silicon-carbon material comprises silicon-carbon particles, and the silicon-carbon particles meet the following conditions:

[0029] (4.1) Volume distribution particle size DV of silicon carbon particles 50 、DV 90 With DV 10 Satisfy: (DV 90 -DV 10 ) / DV 50 1.0~3.0;

[0030] (4.2) The tap density of silicon carbon particles is 0.85 g / cm 3 ~1.1g / cm 3 ;

[0031] (4.3) The specific surface area of ​​silicon carbon particles is 2.0 m 2 / g~8.0m 2 / g.

[0032] In some embodiments of the present application, the silicon-carbon particles satisfy at least one of the following:

[0033] (5.1) Volume distribution particle size DV of silicon carbon particles 50 、DV 90 With DV 10 Meets: DV 50 3μm~30μm;DV 90 ≤60μm; DV 10 >2.0μm;

[0034] (5.2) The tap density of silicon carbon particles is 0.85 g / cm 3 ~1.0g / cm 3 ;

[0035] (5.3) The specific surface area of ​​silicon carbon particles is 3.0 m 2 / g~6.0m 2 / g.

[0036] In some embodiments of the present application, the pore volume of the silicon carbon particles is 0.01 cm 3 / g~0.05cm 3 / g.

[0037] In some embodiments of the present application, the properties of the silicon-carbon material satisfy at least one of the following:

[0038] (6.1) Using silicon carbon material as the negative electrode active material and metallic lithium as the counter electrode, a button cell is assembled. At 25°C, the battery is discharged to 5 mV using a constant current of 0.05C, left to stand for 10 min, and charged to 2.0 V using 0.1C. The initial coulombic efficiency is ≥90%, preferably 94% to 97%;

[0039] (6.2) The powder resistivity of the silicon-carbon material under a pressure of 16 MPa is ≤3 Ω·cm, preferably 1.0 Ω·cm to 1.5 Ω·cm.

[0040] The third aspect of the present application is to provide a method for preparing a silicon-carbon material, comprising the following preparation process:

[0041] preparing porous carbon materials;

[0042] A silicon source is introduced into the porous carbon material, and generated silicon grains are formed in the porous structure of the porous carbon material;

[0043] Stop introducing the silicon source and select to introduce the carbon source to generate a silicon-carbon material including a carbon coating layer.

[0044] In some embodiments of the present application, preparing the porous carbon material includes:

[0045] The carbon material precursor is subjected to high temperature treatment, mixed with an excess of strong alkali and continued to be heated to obtain an alkali-activated material, excess strong alkali in the alkali-activated carbon material is removed, the material is crushed, and small-sized particles are removed to obtain carbon particles.

[0046] In some embodiments of the present application, mixing with an excess of a strong base and then heating to obtain an alkali-activated material comprises:

[0047] The carbon material after high temperature treatment is mixed with a strong base, heated to 900°C to 1000°C in an inert atmosphere, and kept warm for 1h to 12h;

[0048] The mass ratio of the carbon material to the strong base after high temperature treatment is 1:(7-10);

[0049] The strong base includes either sodium hydroxide or potassium hydroxide.

[0050] In some embodiments of the present application, removing excess strong alkali from the material after alkali activation comprises:

[0051] The alkali-activated material is immersed in an acidic solution for full reaction, taken out, washed with water and then dried;

[0052] The acidic solution includes any one of a hydrochloric acid solution, a sulfuric acid solution, and a phosphoric acid solution.

[0053] The fourth aspect of the present application is to provide a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises the porous carbon material disclosed in the first aspect or the silicon-carbon material disclosed in the second aspect or the silicon-carbon material prepared by the preparation method disclosed in the third aspect.

[0054] The fifth aspect of the present application is to provide an electrical device, comprising the secondary battery disclosed in the fourth aspect.

[0055] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0057] Figure 1 A schematic diagram of the battery structure of some embodiments of the present application;

[0058] Figure 2 This is a schematic diagram of the exploded structure of batteries in some embodiments of the present application;

[0059] Figure 3 A schematic diagram of a vehicle structure of some embodiments of the present application;

[0060] Figure 4 A schematic diagram of the structure of a battery pack according to some embodiments of the present application;

[0061] The reference numerals in the specific implementation manner are as follows:

[0062] 10000, vehicles;

[0063] 1000, battery; 2000, controller; 3000, motor;

[0064] 100. Battery cell;

[0065] 200, box body; 210, first part; 220, second part;

[0066] 10. Secondary battery;

[0067] 101. Shell; 102. Electrode assembly; 103. Cover plate. DETAILED DESCRIPTION

[0068] Below, the porous carbon material, silicon-carbon material, secondary battery and electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0069] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0070] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0071] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0072] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0073] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0074] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0075] If not otherwise specified, in this application, the terms "first", "second", etc. are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity, specific order or primary and secondary relationship of the indicated technical features.

[0076] Unless otherwise specified, in this application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple sheets" refers to more than two sheets (including two sheets).

[0077] Unless otherwise specified, the orientations or positional relationships indicated by technical terms such as "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", and "circumferential" are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the embodiments of the present application.

[0078] The specific capacity of silicon is the highest among all known negative electrode materials, reaching 4200mAh / g. However, the silicon-lithium alloy formed by pure silicon during the charging process in lithium-ion batteries will cause the negative electrode material to undergo a huge volume expansion, with an expansion rate of up to 300%, causing the negative electrode material to collapse and pulverize, thereby destroying the battery's safety and cycle performance.

[0079] Porous carbon material is a carbon material with a network structure consisting of interconnected or closed pores, which has strong adsorption properties. It can be used to deposit silicon materials to improve the high energy density of batteries while alleviating a certain degree of expansion of silicon materials. However, the porous carbon materials currently used are still not ideal and are more likely to affect the cycle performance of batteries, limiting the further development of battery technology.

[0080] To solve the above problems, the prior art discloses a variety of methods, such as improving the stability of the structure or physical and chemical properties of porous carbon materials, etc. However, these methods still find it difficult to match the size of silicon materials with the physical and chemical properties of porous carbon materials to improve the cycle performance of batteries.

[0081] If the porous carbon material can maintain a certain stability in its physical and chemical properties and on this basis match the size and / or content of the silicon material, the cyclability of the battery can be improved to a certain extent.

[0082] Based on the above considerations, in order to solve the technical problem of rapid attenuation of battery cyclability caused by the unsatisfactory performance of porous carbon materials in batteries, a porous carbon material, silicon-carbon material, negative electrode sheet, battery, and electrical device were obtained according to the above design concept and related experimental research.

[0083] First, the present application discloses a porous carbon material, which includes carbon particles having a porous structure. Specifically, the porous carbon material meets the following conditions:

[0084] (1.1) The porous structure comprises mesopores and micropores, and the number of mesopores is not less than the number of micropores;

[0085] (1.2) The particle size volume distribution diagram of the carbon particles shows: Dv1 ≥ 0.5 μm;

[0086] (1.3) The specific surface area of ​​porous carbon material is 1400 m 2 / g~1800m 2 / g.

[0087] The porous carbon material provided in the present application has a suitable porous structure, in which the number of mesopores is not less than the number of micropores, because generally speaking, the pore size of the micropores is smaller than the pore size of the mesopores, wherein the micropores are mainly used to facilitate the subsequent deposition of silicon materials, and on the basis of improving the capacity of the porous carbon material, the amount of silicon material deposited can be limited to reduce the effect of the expansion of the silicon material on the porous carbon material structure, thereby affecting the cyclicity of the battery. The mesopores are mainly used to facilitate the volume expansion of the slow-release porous carbon material. When the number of mesopores is greater than or equal to the number of micropores, it can not only limit the expansion degree of the silicon material itself, but also provide sufficient slow-release space for the expansion of the silicon material. On the other hand, by controlling the number of micropores and mesopores in the porous structure to form a porous carbon material with a relatively high specific surface area, the specific surface area of ​​the porous carbon material is larger than that of conventional materials, and the beneficial effects brought by it include: facilitating the subsequent deposition of silicon materials, and conveniently controlling the silicon material content and silicon grain size formed in the porous structure, and also reserving part of the volume space for buffering the expansion of the silicon material. In addition, conventional carbon particles contain small-sized micropowder particles, such as micropowder particles with a particle size of less than 0.5 μm. These micropowder particles are easy to adhere to the surface of carbon particles during the subsequent formation of silicon materials, which directly increases the probability of side reactions between carbon particles and electrolytes. This application removes small-sized micropowder particles and controls the particle size of carbon particles to reduce the impact of side reactions on battery cycle performance. Therefore, the porous carbon material designed in this application improves the battery cycle performance by reducing cycle expansion while maintaining a relatively high first efficiency of the material to increase the number of battery cycles.

[0088] The porous carbon material provided in the present application is used as a substrate for silicon-carbon materials, and is ultimately used to make negative electrode plates and applied to secondary batteries, thereby improving the performance of the battery, such as improving the cyclability at a certain capacity, thereby increasing the user experience. The battery may include an outer packaging. The outer packaging may be used to encapsulate the above-mentioned electrode assembly and electrolyte. The outer packaging of the battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and as plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate, etc. may be listed.

[0089] The present application has no particular limitation on the shape of the battery, which may be cylindrical, square or any other shape. For example, Figure 1 The secondary battery 10 is a square structure as an example.

[0090] According to some embodiments of the present application, Figure 2, the outer packaging may include a shell 101 and a cover plate 103. Among them, the shell 101 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 101 has an opening connected to the receiving cavity, and the cover plate 103 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 102 through a winding process or a lamination process. The electrode assembly 102 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 102. The number of electrode assemblies 102 contained in the secondary battery 10 can be one or more, and those skilled in the art can select according to specific actual needs.

[0091] The electrode assembly provided in the present application is applied to batteries to improve battery performance. The battery can be used as a power source for an electrical device or as an energy storage unit for an electrical device. The electrical device is applied to the power field, such as mobile devices (such as mobile phones, laptop computers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but not limited to the above-mentioned fields.

[0092] For the convenience of explanation, some embodiments of the present application are described by taking a vehicle as an example of an electrical device.

[0093] Please refer to Figure 3 , Figure 3 A schematic diagram of the structure of a vehicle 10000 provided for some embodiments of the present application. The vehicle 10000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 1000 is provided inside the vehicle 10000, and the battery 1000 may be provided at the bottom, head or tail of the vehicle 10000. The battery 1000 may be used to power the vehicle 10000, for example, the battery 1000 may be used as an operating power source for the vehicle 10000. The vehicle 10000 may also include a controller 2000 and a motor 3000, and the controller 2000 is used to control the battery 1000 to power the motor 3000, for example, for the starting, navigation and working power requirements of the vehicle 10000 during driving.

[0094] In some embodiments of the present application, the battery 1000 can not only serve as the operating power source of the vehicle 10000, but also serve as the driving power source of the vehicle 10000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 10000.

[0095] Please refer to Figure 4 , Figure 4The exploded diagram of the battery 1000 provided in some embodiments of the present application. The battery 1000 includes a housing 200 and a battery cell 100. Conventional battery cells include primary batteries or secondary batteries. The present application specifically protects secondary batteries. The battery cell 100 is accommodated in the housing 200. The housing 200 is used to provide a storage space for the battery cell 100. The housing 200 can adopt a variety of structures.

[0096] In some embodiments, the box body 200 may include a first part 210 and a second part 220, the first part 210 and the second part 220 cover each other, and the first part 210 and the second part 220 jointly define a storage space for accommodating the secondary battery 100. The second part 220 may be a hollow structure with one end open, and the first part 210 may be a plate-like structure, and the first part 210 covers the open side of the second part 220, so that the first part 210 and the second part 220 jointly define a storage space; the first part 210 and the second part 220 may also be hollow structures with one side open, and the open side of the first part 210 covers the open side of the second part 220. Of course, the box body 200 formed by the first part 210 and the second part 220 may be in various shapes, such as a cylinder, a cuboid, etc.

[0097] In the battery 1000, there may be multiple battery cells 100, and the multiple battery cells 100 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 100 are both connected in series and in parallel. The multiple battery cells 100 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 100 is accommodated in the box 200; of course, the battery 1000 may also be a battery 1000 module formed by connecting multiple battery cells 100 in series, in parallel, or in a mixed connection, and then the multiple battery 1000 modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 200. The battery 1000 may also include other structures, for example, the battery 1000 may also include a busbar component for realizing electrical connection between the multiple battery cells 100.

[0098] Porous carbon materials

[0099] The present application discloses a porous carbon material in some embodiments. The porous carbon material comprises carbon particles. The carbon particles have a porous structure. Specifically, the porous carbon material satisfies the following conditions:

[0100] (1.1) The porous structure comprises mesopores and micropores, and the number of mesopores is not less than the number of micropores;

[0101] (1.2) The particle size volume distribution diagram of the carbon particles shows: Dv1 ≥ 0.5 μm;

[0102] (1.3) The specific surface area of ​​porous carbon material is 1400 m 2 / g~1800m 2 / g.

[0103] The porous structure in this application includes any conventional meaning in this field, such as conventional porous structures generally include macropores, mesopores and micropores, the pore size of micropores is less than 2nm, the pore size of mesopores is 2nm to 50nm, and the pore size of macropores is greater than 50nm. This application includes using conventional testing instruments in this field to test the distribution of each pore and obtain the specific number of each pore by statistics, such as using the testing instrument ASAP2460-physical adsorption analyzer, placing the porous carbon material sample after drying and degassing in liquid nitrogen, adjusting different test pressures, measuring the adsorption amount of nitrogen respectively, and drawing the adsorption and desorption isotherms. The shape of the pore is determined according to the shape of the hysteresis loop, the pore distribution is calculated according to different pore models, the BJH model is used to fit the pore size distribution curve of the mesopores, and the DFT model is used to fit the pore size distribution curve of the micropores.

[0104] The present application discloses in these embodiments that the porous structure is mainly composed of mesopores and micropores, and the number of mesopores is not less than the number of micropores. This is because generally speaking, the pore size of micropores is smaller than the pore size of mesopores, wherein the micropores are mainly used to facilitate the subsequent deposition of silicon materials. On the basis of improving the capacity of porous carbon materials, the deposition amount of silicon materials can be limited to reduce the influence of the expansion of silicon materials on the structure of porous carbon materials, thereby affecting the cyclability of the battery. The mesopores are mainly used to facilitate the volume expansion of the sustained-release porous carbon materials. When the number of mesopores is greater than or equal to the number of micropores, it can not only limit the expansion degree of the silicon material itself, but also provide sufficient sustained-release space for the expansion of the silicon material. On the other hand, for porous carbon materials, by controlling the number of micropores and mesopores in the porous structure to form a porous carbon material with a relatively high specific surface area, the specific surface area of ​​the porous carbon material is larger than that of conventional materials, reaching 1400m 2 / g~1800m 2 / g; and the specific surface area in this application includes any conventional concept in the art, which can be tested by instruments or methods known in the art, such as using a gas adsorption method to test the specific surface area, specifically referring to the standard test of GB / T19587-2017. The beneficial effects brought about by the porous carbon material with the above-mentioned relatively large specific surface include: it is convenient for the subsequent deposition of silicon materials, it is convenient to control the content of silicon materials and the size of silicon grains formed in the porous structure, and it can reserve part of the volume space for buffering the expansion of silicon materials. In these embodiments, the specific surface area of ​​the porous carbon material includes but is not limited to 1400m 2 / g, 1450m 2 / g、1500m 2 / g, 1550m 2 / g、1600m 2 / g, 1650m 2 / g、1700m 2 / g, 1750m 2 / g、1800m 2 / g or any of the values ​​that satisfy the range.

[0105] The number of micropores and mesopores in the porous structure of the present application affects not only the specific surface area of ​​the porous carbon material, but also the particle size of the carbon particles. Since the number of mesopores in the porous structure of the present application is relatively large, the particle size distribution of the carbon particles is also relatively concentrated. First, the particle size volume distribution diagram of the carbon particles of the present application can be measured by conventional measurement methods in the art, such as using a particle size analyzer to measure the particle size distribution diagram and then obtain it by statistics. In these embodiments, the present application selects to refer to the laser diffraction particle size analysis method for determination, specifically refers to the standard GB / T19077-2016 to obtain the particle size distribution diagram, and then obtains it by calculation. Secondly, conventional carbon particles contain small-sized micropowder particles, such as micropowder particles with a particle size of less than 0.5 μm. This type of micropowder particles is easy to adhere to the surface of the carbon particles during the subsequent formation of silicon materials, which directly increases the probability of side reactions between the carbon particles and the electrolyte. The present application removes the small-sized micropowder particles and controls the particle size of the carbon particles to reduce the impact of side reactions on the battery cycle performance.

[0106] The Dv1 in these embodiments of the present application includes 1% of the volume of particles with a particle size smaller than it, wherein when Dv1 is 0.5 μm, it indicates that the volume of particles with a particle size smaller than 0.5 μm accounts for 1%. The present application chooses to control Dv1≥0.5 μm, which indicates that the content of small-size micropowder particles in the carbon particles is small and reaches a controllable level, thereby improving the concentration of the volume distribution particle size of the carbon particles, and also helps to reduce the impact of side reactions on the battery cycle performance, thereby increasing the number of battery cycles.

[0107] In some embodiments of the present application, the volume distribution particle size of the carbon particles satisfies: Dv1 is 0.5 μm to 1.0 μm.

[0108] The volume distribution particle size Dv1 of the carbon particles in the present application can be any one of 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm or any one of the above range values. The volume distribution particle size Dv1 of the carbon particles in the present application is larger than the conventional value. This is because in the process of preparing the porous carbon material, most of the small-sized micro-powder particles are removed. This type of micro-powder particles is easy to adhere to the surface of the carbon particles during the subsequent formation of the silicon material, which directly increases the probability of side reactions between the carbon particles and the electrolyte. The present application removes small-sized micro-powder particles and controls the particle size of the carbon particles, which is conducive to reducing the impact of side reactions on the battery cycle performance.

[0109] In some embodiments of the present application, the volume distribution particle size DV of the carbon particles is 50 、DV 90 With DV 10 Satisfy the following:

[0110] DV 50 3μm~20μm;DV 90 ≤35μm; DV 10 >1.5μm.

[0111] In these embodiments, the present application further obtains the volume distribution particle size DV of the carbon particles through statistics and calculation based on the particle size volume distribution diagram of the carbon particles. 50 、DV 90 With DV 10 Specific value. Dv90 in this application includes 90% of the volume of particles with a diameter smaller than it, Dv10 includes 10% of the volume of particles with a diameter smaller than it, Dv50 includes 50% of the volume of particles with a diameter larger than it, and 50% of the volume of particles smaller than it. It is also called the median diameter, which is usually used to indicate the average particle size of the particles. Whether it is Dv90, Dv10 or Dv50, conventional measurement methods in the field can be used, such as using a particle size analyzer to measure the particle size distribution and then obtaining it by statistics. In these embodiments, the present application selects to refer to the laser diffraction particle size analysis method for determination, specifically refers to the standard GB / T19077-2016 to obtain the particle size distribution diagram, and then obtains it by calculation. The present application discloses DV in these embodiments. 50 Includes any one of 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm or any one of the values ​​satisfying the above range.

[0112] The volume distribution particle size DV of the carbon particles in this application is 50 、DV 90 With DV 10 Meets: DV 50 3μm~20μm;DV 90 ≤35μm; DV 10 >1.5μm. Carbon particles that meet this particle size distribution condition not only match the number of mesopores and micropores mentioned above, but also facilitate the subsequent formation of silicon materials in the pore structure of the material.

[0113] In some embodiments of the present application, the volume distribution particle size DV of the carbon particles is 505μm~19μm.

[0114] The present application has found through experimental research in these embodiments that when the volume distribution particle size DV of the carbon particles is 50 When the particle size is 5μm to 19μm, the volume distribution particle size of the carbon particles is more concentrated, which can not only better control the side reactions, but also effectively reduce the cycle expansion, thereby significantly increasing the number of battery cycles.

[0115] In some embodiments of the present application, the specific surface area of ​​the porous carbon material is 1450 m 2 / g~1750m 2 / g.

[0116] The present application has found through experimental research in these embodiments that the specific surface area of ​​the porous carbon material is 1450m 2 / g~1750m 2 / g, which not only corresponds to a better match between the number of mesopores and micropores mentioned above, but also better matches the volume distribution particle size of carbon particles.

[0117] In some embodiments of the present application, the porous structure satisfies the following conditions:

[0118] (2.1) The number of mesopores accounts for more than 50% of the number of porous structures;

[0119] (2.2) The number of micropores accounts for less than 50% of the number of porous structures;

[0120] (2.3) The average pore size of the porous structure is 1.0 nm to 10 nm.

[0121] This application can obtain the distribution of each pore through conventional testing methods in the field and obtain the specific number through statistics. In these embodiments, the porous structure is mainly composed of mesopores and micropores, wherein the number of mesopores accounts for more than 50% of the number of porous structures, and the number of micropores accounts for less than 50% of the number of porous structures, so that the porous carbon has a relatively large specific surface area. As mentioned above, the micropores are mainly used to facilitate the subsequent deposition of silicon grains. On the basis of improving the capacity of the porous carbon material, it can also limit the deposition amount of silicon material to reduce the effect of the expansion of the silicon material on the structure of the porous carbon material and thus affect the cyclability of the battery. The mesopores are mainly used to facilitate the slow-release volume expansion of the porous carbon material. When the number of mesopores is greater than or equal to the number of micropores, it can not only limit the expansion degree of the silicon material itself, but also provide sufficient slow-release space for the expansion of the silicon material.

[0122] The average pore size of the porous structure in this application includes any conventional method in the art, including using conventional testing instruments in the art to test the distribution of each pore and obtain the number of each pore by statistics, and then calculating the average pore size through a mathematical function. The pore volume and specific surface area of ​​the porous carbon material can also be obtained by using adsorption and desorption isotherms. According to the model of the relevant pores, the pore volume is divided by the specific surface area and multiplied by the model coefficient to obtain the average pore size; for example, the test instrument used is ASAP2460-physical adsorption analyzer, and the porous carbon material sample after drying and degassing is placed in liquid nitrogen, and different test pressures are adjusted to measure the adsorption amount of nitrogen respectively, and draw adsorption and desorption isotherms.

[0123] In these embodiments, the average pore size of the porous structure obtained by calculation is 1.0nm to 10nm. In these embodiments, the average pore size of the porous structure can be 1.0nm, 1.5nm, 2.0nm, 2.5nm, 3.0nm, 3.5nm, 4.0nm, 4.5nm, 5.0nm, 5.5nm, 6.0nm, 6.5nm, 7.0nm, 7.5nm, 8.0nm, 8.5nm, 9.0nm, 9.5nm, 10nm, or any one of the above range values. The specific value of the pore size of the porous structure and the number of pores in the present application are limited by the treatment conditions of the carbon material precursor by the strong alkali in the preparation process. Generally speaking, the more the strong alkali is used, the higher the treatment temperature, and the longer the time, the more mesopores are produced and the larger the pore size. The present application controls the average pore size of the porous structure to be 1.0 nm to 10 nm, which matches the number of mesopores and micropores, the volume distribution particle size of carbon particles, and the subsequent preparation method, which is beneficial to the subsequent formation of silicon materials.

[0124] In some embodiments of the present application, the porous carbon material satisfies at least one of the following:

[0125] (3.1) The number of mesopores accounts for 50% to 70% of the number of the porous structure;

[0126] (3.2) The number of micropores accounts for 30% to 50% of the number of the porous structure;

[0127] (3.3) The average pore size of the porous structure is 2nm to 8nm;

[0128] The present application further describes in these embodiments that the number of mesopores accounts for 50% to 70% of the number of porous structures, while the number of micropores accounts for 30% to 50% of the number of porous structures, which is beneficial for further ensuring the battery capacity while improving the battery's cyclability.

[0129] The present application discloses in some embodiments that the pore volume of the porous carbon material is 0.8 cm 3 / g~1.4cm3 / g to make it more convenient to make the silicon material in its porous structure. The pore volume in this application is also the pore volume, which includes the measurement using instruments and methods known in the art, for example, it can be tested with reference to GB / T 21650.2-2008. The testing instrument can be the TRISTAR II 3020 specific surface area and porosity analyzer of Micromeritics, USA. The pore volume of the porous carbon material can also be obtained by using adsorption and desorption isotherms; for example, the testing instrument is ASAP2460-physical adsorption analyzer, the porous carbon material sample after drying and degassing is placed in liquid nitrogen, different test pressures are adjusted, the adsorption amount of nitrogen is measured respectively, and the adsorption and desorption isotherms are drawn. The specific values ​​of the pore volume of the porous carbon material in this application are related to the average pore size of the porous structure and the specific surface area of ​​the porous carbon material. In these embodiments, the pore volume of the porous carbon material obtained by testing and calculation in this application is 0.8cm 3 / g~1.4cm 3 / g, under this pore volume, it is convenient for silicon material to form in its porous structure. In these embodiments, the pore volume of the porous carbon material includes but is not limited to 0.8cm 3 / g, 0.9cm 3 / g, 1.0cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g, 1.4cm 3 / g or any of the values ​​satisfying the above ranges.

[0130] The present application focuses on describing the physical and chemical properties of porous carbon materials in the above embodiments. Porous carbon materials that meet the physical and chemical properties need to be matched with silicon materials under certain conditions to form silicon-carbon materials. Therefore, the present application focuses on describing silicon-carbon materials in the following embodiments.

[0131] Silicon Carbon Materials

[0132] The second aspect of the present application discloses a silicon-carbon material, which includes the porous carbon material described in the first aspect, and also includes silicon grains and a carbon coating layer, wherein the silicon grains are formed in the porous structure; and the carbon coating layer is located outside the porous carbon material.

[0133] The silicon grains in this application include any conventional meaning in the art, for example, the silicon grains have a certain crystal form, and the specific crystal form is the conventional silicon crystal form in the art, such as diamond type. The silicon grains include but are not limited to being formed in the porous structure of the porous carbon material by chemical vapor deposition, physical vapor deposition or atomic layer deposition. On the other hand, since the mesopores or micropores of the porous structure are usually through holes, the silicon grains are distributed along the pore walls of the through holes and accumulated to form silicon particles.

[0134] The carbon coating layer of the present application includes a carbon material layer arranged along the outer surface of the porous carbon material to form an outer shell layer that wraps the porous carbon material. The outer shell layer can reduce the probability of silicon grains contacting with the outside air and being oxidized, and can reduce the probability of silicon grains contacting with the electrolyte to improve the cyclability of the battery. The present application also discloses in these embodiments that the carbon material forming the carbon coating layer includes amorphous carbon, and the thickness of the carbon coating layer formed by the amorphous carbon is 30nm to 200nm.

[0135] The carbon coating layer of the present application comprises a continuous and complete coating layer, and the carbon coating layer is used to separate the silicon crystal grains from the external electrolyte as much as possible to reduce the probability of the silicon crystal grains and the electrolyte contacting and reacting.

[0136] In the silicon-carbon material provided by the present application, silicon grains are mainly formed in the micropores of the porous carbon material to facilitate the control of the specific content, and most of the reserved mesopores are mainly used as volume space to buffer the expansion of the silicon material. The outer shell layer can reduce the probability of silicon grains contacting with the outside air and then being oxidized, and on the other hand, it can reduce the probability of silicon grains contacting and reacting with the electrolyte. Therefore, the silicon-carbon material designed by the present application can largely limit the volume expansion of the silicon material during the lithium insertion and extraction process to improve the cyclability of the battery.

[0137] In some embodiments of the present application, the silicon-carbon material contains silicon element, and the mass percentage content of the silicon element is 30% to 40% based on the total mass of the silicon-carbon material.

[0138] In some embodiments of the present application, the mass percentage of silicon element is 35% to 40%.

[0139] In the present application, the amount of silicon grains formed in the porous structure affects not only the capacity of the battery, but also its expansion degree and the probability of reacting with the electrolyte. Generally speaking, the more silicon grains are formed, the more beneficial it is to the capacity of the battery, but the greater its own expansion in the lithium insertion and extraction cycle, the greater the probability of reacting with the electrolyte. Limited by the number of mesopores and micropores in the above-mentioned porous structure, and the pore size of the porous structure, etc. The present application chooses to control the mass percentage content of silicon element to be 30% to 40%. In these embodiments, the mass percentage content of silicon element includes but is not limited to any one of 30%, 32%, 35%, 38%, 40% or any one of the above-mentioned range values.

[0140] The present application discloses in some embodiments that the silicon-carbon material further comprises carbon element, and the mass percentage content of the carbon element is 60% to 70% based on the total mass of the silicon-carbon material.

[0141] The present application discloses, in some embodiments, that silicon grains are formed in the micropores of a porous structure. The present application controls the formation conditions of silicon grains so that as many silicon grains as possible are formed in the micropores of a porous structure. As mentioned above, the number of micropores in the porous structure is less than the number of mesopores, which means that the amount of silicon grains formed can be controlled. The present application ultimately achieves the control of the mass percentage content of silicon element to 30% to 40%. At the same time, the carbon precursor of the present application is subjected to high-temperature impurity removal treatment when used to prepare silicon-carbon materials, so the content of other impurity elements is almost not considered.

[0142] The present application discloses that in some embodiments, the grain size of silicon grains is ≤8.0 nm.

[0143] The present application discloses in some embodiments that the grain size of silicon grains is 5.0 nm to 8.0 nm.

[0144] The silicon grain size of the present application can be calculated using an X-ray diffraction pattern or obtained by characterization through a transmission electron microscope. When describing the porous carbon material above, the present application discloses that the average pore size of the porous structure is 1.0nm to 10nm. At the same time, the silicon grains are distributed along the inner walls of the micropores to stack to form silicon particles. The silicon particles can be spherical, quasi-spherical, etc. The silicon particles are further stacked to form a sheet-like film layer distributed along the inner wall of the through hole. Therefore, there is no direct relationship between the grain size of the silicon grains of the present application and the pore size of the porous structure. In these embodiments, the grain size of the silicon grains includes but is not limited to any one of 8.0nm, 7.5nm, 7.0nm, 6.5nm, 6.2nm, 6.0nm, 5.0nm or any one of the above range values.

[0145] The present application discloses in some embodiments that the silicon-carbon material comprises silicon-carbon particles, and the silicon-carbon particles meet the following conditions:

[0146] (4.1) Volume distribution particle size DV of silicon carbon particles 50 、DV 90 With DV 10 Satisfy: (DV 90 -DV 10 ) / DV 50 1.0~3.0;

[0147] (4.2) The tap density of silicon carbon particles is 0.85 g / cm 3 ~1.1g / cm 3 ;

[0148] (4.3) The specific surface area of ​​silicon carbon particles is 2.0 m 2 / g~8.0m 2 / g.

[0149] The silicon-carbon material in the present application includes silicon-carbon particles, and the silicon-carbon particles have a certain particle size, specific surface area, and tap density. As mentioned above, Dv90 in the present application includes 90% of the volume of particles with a particle size smaller than it, Dv10 includes 10% of the volume of particles with a particle size smaller than it, and Dv50 includes 50% of the volume of particles with a particle size larger than it, and 50% of the volume of particles smaller than it, which is also called the median diameter, and is usually used to indicate the average particle size of the particles. Whether it is Dv90, Dv10 or Dv50, conventional measurement methods in the field can be used, such as using a particle size analyzer to measure the particle size distribution and then obtain it by statistics. In these embodiments, the present application chooses to refer to the laser diffraction particle size analysis method for determination, specifically refers to the standard GB / T19077-2016 to obtain the particle size distribution diagram, and then obtains it by calculation. The volume distribution particle size DV of the silicon-carbon particles controlled in the present application is 50 、DV 90 With DV 10 Satisfy: (DV 90 -DV 10 ) / DV 50 The ratio of DV to 1.0 is 1.0 to 3.0, so that the silicon-carbon composite particles of different sizes are properly matched to reduce the expansion of the silicon-carbon material during the lithium insertion and extraction process. 90 -DV 10 ) / DV 50 The value of includes but is not limited to any one of 1.0, 1.2, 1.5, 1.8, 2.0, 2.2, 2.5, 2.8, 3.0 or any one of the values ​​satisfying the above range.

[0150] The tap density in this application includes any common concept in the art, which can be obtained by testing using instruments or methods known in the art, such as by testing with reference to standard GB / T5162-2006. In these examples, the tap density of silicon-carbon particles tested in this application is 0.85 g / cm 3 ~1.1g / cm 3 To ensure the capacity of the battery, in these embodiments, the tap density of the silicon-carbon particles includes but is not limited to 0.85 g / cm 3 , 0.9g / cm 3 , 0.95g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 Any one of the values ​​or any one of the values ​​satisfying the above range.

[0151] The specific surface area in this application includes any conventional concept in the art, which can be obtained by testing using instruments or methods known in the art, such as using a gas adsorption method to test the specific surface area, specifically referring to the standard test of GB / T19587-2017. The specific surface area of ​​the silicon-carbon particles tested in these embodiments is 2.0 m 2 / g~8.0m 2 / g, the specific value of the specific surface area of ​​the silicon-carbon particles is mainly affected by the volume distribution particle size and tap density of the silicon-carbon particles. In these embodiments, the specific surface area of ​​the silicon-carbon particles includes but is not limited to 2.0 m 2 / g, 5.0m 2 / g, 8.0m 2 / g or any of the above ranges. In some embodiments, the present application discloses that the silicon-carbon material comprises silicon-carbon particles, and the silicon-carbon particles satisfy at least one of the following:

[0152] (5.1) Volume distribution particle size DV of silicon carbon particles 50 、DV 90 With DV 10 satisfy:

[0153] DV 50 3μm~30μm;DV 90 ≤60μm; DV 10 >2.0μm;

[0154] (5.2) The tap density of silicon carbon particles is 0.85 g / cm 3 ~1.0g / cm 3 ;

[0155] (5.3) The specific surface area of ​​silicon carbon particles is 3.0 m 2 / g~6.0m 2 / g.

[0156] In some embodiments of the present application, DV is calculated based on the volume distribution particle size diagram of specific silicon-carbon particles. 50 3μm~30μm;DV 90 ≤60μm; DV 10 >2.0μm. Among them, the volume distribution particle size DV of silicon carbon particles 50 The silicon-carbon particles have a volume distribution particle size that satisfies the above specific numerical range, which is conducive to conveniently controlling the side reactions between the silicon-carbon particles and the electrolyte.

[0157] At the same time, in some embodiments of the present application, the tap density of the silicon carbon particles is 0.85 g / cm 3 ~1.0g / cm 3 This was discovered during specific experimental research. On the premise of matching the particle size of silicon-carbon particles, it is beneficial to take into account both the capacity and cyclability of the battery.

[0158] In addition, in some embodiments of the present application, the specific surface area of ​​the silicon-carbon particles is 3.0 m 2 / g~6.0m 2 / g, which shows that an appropriate amount of silicon material has been deposited in the porous structure of the porous carbon material, and at the same time, a part of space can be reserved for convenient sustained release.

[0159] In some embodiments of the present application, the pore volume of the silicon carbon particles is 0.01 cm 3 / g~0.05cm 3 / g.

[0160] The pore volume of the silicon-carbon material in the present application is also the pore volume, which can be measured by instruments and methods known in the art, for example, it can be tested with reference to GB / T 21650.2-2008. The testing instrument can be the TRISTAR II 3020 surface area and porosity analyzer of Micromeritics, USA. The pore volume of the porous carbon material can also be obtained by using adsorption and desorption isotherms; for example, the testing instrument is ASAP2460-physical adsorption analyzer, the silicon-carbon material sample after drying and degassing treatment is placed in liquid nitrogen, different test pressures are adjusted, the adsorption amount of nitrogen is measured respectively, and the adsorption and desorption isotherms are drawn. The pore volume of the silicon-carbon particles tested in these embodiments of the present application is 0.01cm3 / g~0.05cm 3 / g, which indicates that after the silicon material has been formed in the porous structure, some volume space can be reserved for buffering the expansion of the silicon material to improve the cyclability of the battery. In these embodiments, the pore volume of the silicon-carbon particles includes but is not limited to 0.01cm 3 / g, 0.02cm 3 / g, 0.03cm 3 / g, 0.04cm 3 / g, 0.05cm 3 / g or any of the values ​​satisfying the above ranges.

[0161] The present application discloses, in some embodiments, properties of silicon-carbon materials, which specifically satisfy at least one of the following:

[0162] (6.1) A button cell is formed by using silicon-carbon material as the positive electrode active material and metallic lithium as the counter electrode. At 25°C, the cell is discharged to 5 mV using a constant current of 0.05 C, left to stand for 10 min, and charged to 2.0 V using 0.1 C. The first coulombic efficiency is ≥ 90%, preferably 94% to 97%;

[0163] (6.2) The powder resistivity of the silicon-carbon material under a pressure of 16 MPa is ≤3 Ω·cm, preferably 1.0 Ω·cm to 1.5 Ω·cm.

[0164] The first coulombic efficiency in this application includes the first charge and discharge experiment of the assembled button cell under certain test conditions to obtain the first discharge capacity and the first charge capacity, then the first coulombic efficiency = first discharge capacity / first charge capacity × 100%. This application has been tested to obtain a first coulombic efficiency of ≥90% to verify that the use of the silicon-carbon material designed in this application does guarantee the first efficiency of the battery. In specific experimental research, it was also found that the first coulombic efficiency of some silicon-carbon materials was between 94% and 97%, which shows that the silicon-carbon material provided in this application is conducive to improving the first efficiency.

[0165] The powder resistivity of the silicon-carbon material in this application is different from the resistivity of the pole piece, which is mainly used to characterize the conductivity of the silicon-carbon material itself. The powder resistivity in this application includes any conventional concept in the art, such as placing an appropriate amount of silicon-carbon material in the feeding cup of the resistivity tester, applying pressure, manually collecting data, recording the powder resistivity test results at different pressure points and then taking the average value, and the test pressure is 16MPa. The powder resistivity of the silicon-carbon material under a pressure of 16MPa is ≤3Ω·cm in this application after testing, indicating that the amount of silicon material formed in this application is appropriate and effective, because in the silicon-carbon material, the porous carbon material has good conductivity, while the conductivity of the silicon material is weak. In order to improve the performance of the battery, the expansion of the silicon-carbon material needs to be controlled, that is, the content of the silicon material needs to be controlled. In the subsequent specific embodiments of this application, it is found that when the powder resistivity of the silicon-carbon material under a pressure of 16MPa is ≤3Ω·cm, the degree of expansion it exhibits is within a controllable range, so it is also beneficial to the improvement of battery performance. This also shows that the amount of silicon material formed is also appropriate.

[0166] In order to better explain the structure and properties of the above silicon-carbon material, a detailed description is given below in conjunction with its preparation method.

[0167] Preparation method of silicon carbon material

[0168] The third aspect of the present application is to disclose a method for preparing a silicon-carbon material, which comprises the following preparation process:

[0169] preparing porous carbon materials;

[0170] A silicon source is introduced into the porous carbon material, and generated silicon grains are formed in the porous structure of the porous carbon material;

[0171] Stop introducing the silicon source and select to introduce the carbon source to generate a silicon-carbon material including a carbon coating layer.

[0172] In some embodiments of the present application, preparing the porous carbon material includes:

[0173] The carbon material precursor is subjected to high temperature treatment, mixed with an excess of strong alkali and continued to be heated to obtain an alkali-activated material, excess strong alkali in the alkali-activated carbon material is removed, the material is crushed, and small-sized particles are removed to obtain carbon particles.

[0174] In some embodiments of the present application, a carbon material precursor is subjected to high temperature treatment to remove volatile substances. The specific process includes:

[0175] Place the carbon material precursor in an inert atmosphere, heat it to 400°C to 800°C, and keep it warm for 1h to 12h;

[0176] Preferably, the temperature is raised to 400° C. to 700° C. and kept warm for 2 h to 10 h.

[0177] The heating temperature and holding time of the present application all affect the effect of removing volatile substances. The present application discloses in these embodiments that the heating rate is 2°C / min to 8°C / min. In some embodiments of the present application, the carbon material precursor includes but is not limited to asphalt-based porous carbon materials, asphaltene-based porous carbon materials, coal-based porous carbon materials, coke-based porous carbon materials, biochar-based porous carbon materials, carbon black-based porous carbon materials, oil product-based porous carbon materials, tar-based porous carbon materials, polymer-based porous carbon materials, protein-based porous carbon materials, carbohydrate-based porous carbon materials, cotton-based porous carbon materials, fat-based porous carbon materials, waste-based porous carbon materials, graphite-based porous carbon materials, melamine-based porous carbon materials, wood-based porous carbon materials, porous graphene, porous graphene oxide, activated carbon, and combinations thereof. The carbon material precursor of this type is easy to obtain a porous carbon material with the above-mentioned particle size, specific surface area, tap density, and compacted density in the above-mentioned preparation process.

[0178] In some embodiments of the present application, the inert atmosphere includes using conventional inert gases in the art to create an inert atmosphere, such as rare gases corresponding to Group 0 in the periodic table.

[0179] In some embodiments of the present application, the carbon material precursor is placed in a muffle furnace containing an inert atmosphere for a temperature-raising heating treatment.

[0180] In some embodiments of the present application, the material is mixed with a strong base and then heated to obtain an alkali-activated material, wherein the alkali-activated material satisfies the above-mentioned porous structure characteristics. The specific process includes:

[0181] The carbon material after high temperature treatment is mixed with a strong base, heated to 900°C to 1000°C in an inert atmosphere, and kept warm for 1h to 12h;

[0182] Preferably, heating to 950°C to 1000°C and keeping the temperature for 4h to 12h;

[0183] Preferably, the mass ratio of the carbon material to the strong base after high temperature treatment is 1:(7-10);

[0184] Preferably, the strong base comprises any one of sodium hydroxide and potassium hydroxide.

[0185] The alkali activation reaction temperature in the present application can be any one of 900°C, 950°C, 960°C, 970°C, 980°C, 990°C, 1000°C or any one of the above ranges.

[0186] The alkali activation time in the present application can be any one of 1h, 2h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or any one of the above range values.

[0187] The mass ratio of the carbon material after high temperature treatment to the strong base in the present application can be any one of 1:7, 1:8, 1:9, 1:10 or any one of the values ​​within the above range.

[0188] In these embodiments of the present application, the reaction temperature after alkali activation is controlled to be 900°C to 1000°C, and the amount of strong alkali used is relatively excessive, so it is beneficial to form pores in the carbon material after high temperature treatment, and the number of mesopores in the formed porous structure is controlled to be greater than or equal to the number of micropores. In some embodiments of the present application, removing excess strong alkali from the carbon material after alkali activation includes: immersing the carbon material after alkali activation in an acidic solution for sufficient reaction, taking it out, washing it with water, and drying it. In these embodiments, the acidic solution includes any one of hydrochloric acid solution, sulfuric acid solution, and phosphoric acid solution. The present application prefers hydrochloric acid solution, and the concentration of the hydrochloric acid solution is not high, including but not limited to 0.05mol / L to 0.2mol / L. In the hydrochloric acid solution, the excess unreacted strong alkali is reacted and remains in the solution, and does not affect the morphology of the porous structure.

[0189] The present application discloses in these embodiments that the drying process can be carried out in any conventional apparatus in the art, such as in an oven, and the temperature of the oven is controlled to be no higher than 100°C.

[0190] In some embodiments of the present application, the dried carbon material is crushed to a suitable particle size, and then subjected to classification treatment to remove small particle size particles. The present application discloses the use of an airflow pulverizer for pulverization in these embodiments. The model of the airflow pulverizer includes any conventional model in the art. The volume distribution particle size DV of the carbon particles obtained after the airflow pulverizer treatment in the present application is 50 、DV 90 With DV 10 satisfy:

[0191] DV 50 3 μm to 20 μm, preferably 5 μm to 19 μm;

[0192] DV 90 ≤35μm, preferably 25μm to 30μm;

[0193] DV 10 >1.5μm, preferably 2.0μm~2.5μm;

[0194] Dv1 ≥ 0.5 μm, preferably 0.5 μm to 1.0 μm.

[0195] In the present application, the particle size distribution of the carbon particles obtained after being processed by the air flow mill is relatively concentrated, and the content of small-sized particles is small, which is not only conducive to the subsequent formation of silicon materials, but also can reduce the probability of small-sized particles adhering to the surface of carbon particles during the formation of silicon materials, and directly reduce the probability of side reactions between carbon particles and electrolyte.

[0196] The present application discloses in some embodiments that the reaction conditions for generating silicon grains include the following:

[0197] (7.1) The reaction temperature is 400°C to 750°C, and the time for introducing the silicon source is 1h to 12h; preferably, the reaction temperature is 500°C to 700°C; preferably, the time for introducing the silicon source is 5h to 8h;

[0198] (7.2) The silicon source comprises a silicon source gas and an inert gas, wherein the volume ratio of the silicon source gas to the inert gas is 1:(4-6);

[0199] (7.3) The ventilation volume of the silicon source is 0.2L / min~1.5L / min.

[0200] The present application also discloses in these embodiments that the silicon source includes a silicon source gas and an inert gas, wherein the volume of the silicon source gas accounts for 13% to 20% based on the total volume of the silicon source; in these embodiments, the ventilation volume of the silicon source is controlled to be about 0.2L / min to 1.5L / min, and the types of silicon source gas include but are not limited to monosilane, disilane, etc. The present application also discloses in these embodiments that the porous carbon material is placed in a CVI device and the reaction conditions are controlled to generate silicon grains, the CVI device includes a fluidized bed, and also includes any one of a rotary kiln, a push plate furnace or a tubular furnace; and in the process of generating silicon grains, the pressure in the device is controlled to be within a slightly positive pressure range, such as about 200Pa to 600Pa higher than the atmospheric pressure.

[0201] The present application discloses in some embodiments that the reaction conditions for generating the carbon coating layer include the following:

[0202] (8.1) The reaction temperature is 700°C to 850°C, and the carbon source is continuously introduced for 1h to 6h;

[0203] (8.2) The carbon source comprises a carbon source gas and an inert gas, wherein the volume of the carbon source gas accounts for 5% to 15% based on the total volume of the carbon source;

[0204] (8.3) The ventilation rate of the carbon source is 1.0L / min~3.0L / min.

[0205] In these embodiments, the types of carbon source gas include but are not limited to methane, ethylene, acetylene, etc.

[0206] In these examples, the present application controls the ventilation rate of the carbon source gas to be about 1.0 L / min to 3.0 L / min to generate a carbon coating layer with a thickness of 20 nm to 300 nm.

[0207] Negative electrode

[0208] In some embodiments of the present application, a negative electrode sheet is disclosed, which includes a negative electrode current collector and a negative electrode film layer located on at least one side of the negative electrode current collector. The negative electrode film layer includes a silicon-carbon material as a negative electrode active material, and also includes other negative electrode active materials, such as carbonaceous materials, specifically including but not limited to one or a combination of two or more of artificial graphite, natural graphite, soft carbon, and hard carbon. Among them, artificial graphite, natural graphite, soft carbon, hard carbon, etc. include materials of any form conventional in the art, and include any conventional manufacturers and models in the art. The mass ratio of the negative electrode active material in the negative electrode film layer is 70% to 100%.

[0209] In some embodiments of the present application, it is disclosed that the negative electrode film layer also includes a conductive agent, a thickener, a binder, etc., wherein the conductive agent includes but is not limited to one or a combination of two of graphite, superconducting carbon, carbon black (such as acetylene black, Ketjen black, Super P, etc.), carbon dots, carbon nanotubes, graphene and carbon nanofibers; the thickener includes cellulose and its sodium salt, and cellulose includes methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, etc.; the binder includes but is not limited to polyvinyl alcohol, polyethylene glycol, sodium carboxymethyl cellulose, polyethylene oxide, polyacrylic acid, polyacrylamide, sodium alginate, styrene-butadiene rubber (SBR), etc.

[0210] The negative electrode current collector of the present application may be a metal foil or a composite current collector, the metal foil may be a copper foil, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and the like.

[0211] In some embodiments, the present application discloses the mass ratios of silicon-carbon material, conductive agent, thickener and binder in the negative electrode film layer: (93.8% to 95%): (0.2% to 2.0%): (0.2% to 2.0%): (1.2% to 2.2%).

[0212] The present application discloses in some embodiments that the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry, wherein the solid content of the negative electrode slurry is 30wt% to 70wt%, and the viscosity at room temperature is adjusted to 2000mPa·s to 10000mPa·s; the obtained negative electrode slurry is coated on the surfaces of both sides of the negative electrode current collector, and after a drying process, cold pressing such as rolling is performed to obtain a negative electrode sheet. The unit surface density of the negative electrode powder coated on one side is 75mg / m 2 ~220 mg / m 2 , the compaction density of the negative electrode is 1.2g / m 3 ~2.0g / m 3 .

[0213] Positive electrode

[0214] In some embodiments of the present application, a positive electrode sheet is disclosed, which includes a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector. The positive electrode film layer in the present application includes positive electrode active particles, a positive electrode conductive agent, a positive electrode binder, etc. The present application does not specifically limit the specific types of positive electrode active particles. For example, when the positive electrode sheet is applied to a lithium-ion battery, the positive electrode active particles include but are not limited to LiCoO 2 、LiNiO 2 、LiMnO 2 、LiMn 2 O 4 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (NCM111), LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523), LiNi 0.6 CO 0.2 Mn 0.2 O 2 (NCM622), LiNi 0.8 CO 0.1 Mn 0.1 O 2 (NCM811), LiNi 0.85 CO 0.15 Al 0.05 O 2 、LiFePO 4 (LFP) and LiMnPO 4 One or more of the following.

[0215] For example, when the positive electrode is used in a sodium ion battery, the positive electrode active particles include but are not limited to at least one of sodium transition metal oxides, polyanionic compounds, and Prussian blue compounds. Among them, in the sodium transition metal oxide, the transition metal can be one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO 2 , wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1. Polyanionic compounds include sodium vanadium trifluorophosphate (Na 3 V 2 (PO 4 ) 2 F 3 ), sodium vanadium fluorophosphate (NaVPO 4 F), sodium vanadium phosphate (Na 3 V 2 (PO 4 ) 3 ), Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 、NaFePO 4 , one or more of the following. Prussian blue compounds are Na x M 1 M 2 (CN) 6 , where M 1 、M 2 It is one or more of Fe, Mn, Co, Ni, Cu, Zn, Cr, Ti, V, Zr and Ce, wherein 0<x≤2.

[0216] The positive electrode conductive agent includes but is not limited to one or more combinations of graphite, superconducting carbon, carbon black (such as acetylene black, Ketjen black, Super P, etc.), carbon dots, carbon nanotubes, graphene and carbon nanofibers. The positive electrode binder includes but is not limited to one or more combinations of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorine-containing acrylate resin, styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid, carboxymethyl chitosan, etc.

[0217] The positive electrode current collector in the present application may be a metal foil or a composite current collector, wherein the metal foil may be an aluminum foil, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0218] In some embodiments of the present application, a method for preparing a positive electrode sheet is provided: the components for preparing a positive electrode sheet, such as a positive electrode active material, a conductive agent, a binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, wherein the solid content of the positive electrode slurry is 40wt% to 80wt%, and the viscosity at room temperature is adjusted to 5000mPa·s to 25000mPa·s, the positive electrode slurry is coated on both sides of the positive electrode collector, and after drying, the positive electrode sheet is formed by cold rolling; the unit surface density of the positive electrode powder coated on one side is 15mg / m 2 ~35 mg / m 2 The compaction density of the positive electrode is 3.0g / cm 3 ~3.6g / cm 3 , optional 3.3g / cm 3 ~3.5g / cm 3 The calculation formula of compaction density is compaction density = coating surface density / (thickness of the electrode sheet after extrusion × thickness of the current collector).

[0219] Electrolytes

[0220] In some embodiments of the present application, an electrolyte is disclosed, which includes a sodium salt or a lithium salt and an organic solvent, and the organic solvent can be an organic solvent commonly used in the art for electrolyte. As an example, the organic solvent can be selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE) at least one or two combinations. The sodium salt or lithium salt may be a sodium salt or lithium salt commonly used in the art for electrolyte, such as sodium hexafluorophosphate, lithium hexafluorophosphate, etc. The concentration of the electrolyte salt is usually 0.5 mol / L to 5 mol / L.

[0221] Isolation film

[0222] According to some embodiments of the present application, the battery not only includes a negative electrode sheet, a positive electrode sheet and an electrolyte, but also includes a separator stacked together. The stacking method includes but is not limited to the conventional winding or stacking in the art. The material, size, etc. of the separator include but are not limited to any conventional form in the art. Similarly, the material, size, etc. of the positive electrode sheet include but are not limited to any conventional form in the art. For example, the separator is arranged between the positive electrode sheet and the negative electrode sheet to play an isolating role. The separator includes a substrate and also includes a functional coating provided on at least one surface of the substrate. The functional coating can be used to improve the heat resistance, mechanical strength, etc. of the separator. For example, the functional coating may also include other functional materials (such as ceramic particles, other polymers, etc.). Ceramic particles include but are not limited to boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, etc.; the present application has no particular restrictions on the type of the separator substrate, and any known substrate that can be used for the secondary battery separator can be selected. In some embodiments, the separator substrate includes but is not limited to a single-layer film or a multi-layer composite film of one or more of glass fiber, non-woven fabric, polyethylene, and polypropylene. The thickness of the separator is 6μm to 40μm, preferably 12μm to 20μm.

[0223] [Preparation of silicon-carbon materials]

[0224] The present application discloses in some embodiments a method for preparing a silicon-carbon material, comprising the following preparation steps:

[0225] S1. Take 1 kg of cotton-based porous carbon material and put it in a muffle furnace. Pass helium and heat it to 600°C at a heating rate of 5°C / min. Keep it at that temperature for 2 hours. After the furnace cools down, take out the pretreated carbon material.

[0226] S2, taking the pretreated carbon material and potassium hydroxide in a mass ratio of 1:8, mixing them and continuing to place them in a muffle furnace, introducing helium, heating them to 1000° C. at a heating rate of 5° C. / min, and keeping the temperature for 4 hours to obtain an alkali-activated carbon material;

[0227] S3, immersing the alkali-activated carbon material in a 0.1 mol / L hydrochloric acid solution for about 1 hour to remove residual potassium hydroxide, then washing with water, and heating and drying at 80° C. for 12 hours to obtain a dry carbon material;

[0228] S4, grinding the dried carbon material to a suitable particle size by a jet mill to obtain carbon particles having a volume distribution particle size satisfying: Dv1 ≥ 0.5 μm; and other physical and chemical properties of the carbon particles are shown in Table 1;

[0229] S5, placing the carbon particles with concentrated particle size in a CVD rotary furnace, controlling the ventilation volume of the mixed gas to be about 0.2L / min to 1.5L / min according to the ratio of monosilane to helium = 16.7%:83.3%, controlling the heating rate to be 5°C / min to 660°C, and depositing for 8 hours to generate silicon grains;

[0230] S6, stop introducing silicon source gas, continue to introduce carbon source gas (acetylene), control acetylene to about 10%, control acetylene ventilation to about 1.0L / min to 3.0L / min, control heating rate to 5℃ / min to 700℃, react for 4h, generate carbon coating layer, wherein the thickness of carbon coating layer is about 50nm.

[0231] Among them, Examples 1 to 11 are prepared according to the process parameters listed in Table 1 to obtain the porous carbon materials shown in Table 2 and the silicon-carbon materials shown in Tables 3 and 4.

[0232] Comparative Example 1

[0233] A silicon-carbon material is provided, which is different from Example 1 in that S5 is directly performed after S3, and since small-sized particles are not removed, the volume distribution particle size Dv1 of the obtained carbon particles is 0.45 μm, and the specific surface area of ​​the carbon material of the silicon-carbon material in Comparative Example 1 is smaller than that of the present application. See Table 2 for details.

[0234] Comparative Example 2

[0235] A silicon-carbon material is provided, which is different from Example 1 in that the mass ratio of the pretreated carbon material to potassium hydroxide is controlled to be 1:6 in S2, and S3 for removing excess strong alkali is missing. The number of mesopores in the carbon particles in the subsequent silicon-carbon material is less than the number of micropores, and the specific surface area of ​​the carbon material of the silicon-carbon material in Comparative Example 2 is larger than that in Example 1 of the present application. See Table 2 for details.

[0236] Comparative Example 3

[0237] A silicon-carbon material is provided, which is different from Example 1 in that the mass ratio of the pretreated carbon material to potassium hydroxide in S2 is controlled to be 1:2, and S3 for removing excess strong alkali is missing. The number of mesopores in the carbon particles in the subsequent silicon-carbon material is less than the number of micropores, and the specific surface area of ​​the carbon material of the silicon-carbon material in Comparative Example 3 is larger than that in Example 1 of the present application. See Table 2 for details.

[0238] Table 1 Process parameters list

[0239]

[0240] In Examples 2 to 6 of the present application, the processes of steps S2, S4, S5 and S6 are controlled to be different from those of Example 1, so that the number of mesopores and micropores in the porous structure, the average pore size of the porous structure, the pore volume and the volume distribution particle size of the porous carbon material are different from those of Example 1. In Examples 7 to 11, steps S5 and S6 are adjusted to make the silicon crystal grains formed have different sizes, and the volume distribution particle size, tap density, specific surface area and pore volume of the silicon-carbon particles are different from those of Example 1.

[0241] Table 2 List of porous carbon materials

[0242]

[0243] Table 3 List of silicon carbon materials (I)

[0244]

[0245]

[0246] Table 4 List of silicon carbon materials (II)

[0247]

[0248] ①Particle size test:

[0249] Refer to the standard GB / T19077-2016: obtain the volume particle size distribution curve of carbon particles or silicon-carbon particles, take the particle size corresponding to 50% of the cumulative volume distribution percentage as the average particle size Dv50, take the particle size corresponding to 1% of the cumulative volume distribution percentage as the average particle size Dv1, take the particle size corresponding to 90% of the cumulative volume distribution percentage as the average particle size Dv90, take the particle size corresponding to 10% of the cumulative volume distribution percentage as the average particle size Dv10. The test instrument can be the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK.

[0250] ②Specific surface area test:

[0251] Referring to the standard GB / T19587-2017: The obtained carbon particles or silicon-carbon particles are tested by nitrogen adsorption specific surface area analysis test method, and the specific surface area is calculated by BET (Brunauer Emmett Teller) method. The test instrument can be TRISTAR II 3020 specific surface area and porosity analyzer of Micromeritics, USA.

[0252] ③Pore volume test:

[0253] The obtained carbon particles or silicon-carbon particles are tested according to the GB / T21650.2-2008 test method. The testing instrument can be a TRISTAR II 3020 specific surface area and porosity analyzer from Micromeritics, USA.

[0254] ④Tap density test:

[0255] Reference standard GB / T5162-2006.

[0256] ⑤Porous structure quantity test:

[0257] The test instrument used is ASAP2460-physical adsorption analyzer. The carbon particle sample after drying and degassing is placed in liquid nitrogen. Different test pressures are adjusted to measure the adsorption amount of nitrogen, and the adsorption and desorption isotherms are drawn. The shape of the pores is determined according to the shape of the hysteresis loop, and the pore distribution is calculated according to different pore models. The pore size distribution curve of the mesopore is fitted using the BJH model, and the pore size distribution curve of the micropore is fitted using the DFT model. Then it is obtained by statistical calculation.

[0258] ⑥ Pore size test of porous structure:

[0259] In the above ⑤ test on the number of porous structures, the pore size distribution curve of each pore is obtained, the specific surface area is obtained in ②, and the pore volume is obtained in ③. According to the model of the relevant pores in ⑤, the average pore size is obtained by dividing the pore volume by the specific surface area and multiplying by the model coefficient.

[0260] ⑦ Silicon grain size test:

[0261] A double-beam focused ion beam microscope is used to cut a sample from the core of the silicon material particle to obtain a cross-sectional image of the silicon material particle, and then a high-resolution transmission electron microscope is used to observe and calculate the grain size of the crystalline silicon material. In the obtained cross-sectional image, the area with lattice fringe characteristics is taken as a grain, the diameter of the area is taken as the grain size, and the average value of at least 50 grain sizes is taken as the test result. The test instrument can be the Helios5CX focused ion beam / scanning electron microscope dual-beam system of Thermo Fisher Scientific and the Spectra S / TEM scanning transmission electron microscope of Thermo Fisher Scientific.

[0262] ⑧Silicon content test:

[0263] Refer to GB / T 20975.5-2020 to test the silicon content in the negative electrode active material.

[0264] ⑨Powder resistivity test under 16Mpa:

[0265] Place an appropriate amount of silicon-carbon material in the feeding cup of the resistivity tester, apply pressure, collect data manually, record the powder resistivity test results at different pressure points and then take the average value. The test pressure is 16 MPa.

[0266] ⑩First Coulomb efficiency test:

[0267] 1. Preparation of button cells:

[0268] 1. Negative electrode:

[0269] The silicon-carbon composite material, conductive carbon black and binder polyacrylic acid prepared above are mixed in a mass ratio of 8:1:1, and deionized water is added and stirred to form a negative electrode slurry; the negative electrode slurry is evenly coated on one surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.

[0270] 2. Electrolyte:

[0271] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 20:20:60, and then LiPF 6 Evenly dissolved in the above solution, and adding additive fluoroethylene carbonate (FEC) to obtain an electrolyte. In the electrolyte, LiPF 6 The concentration is 1 mol / L, and the mass proportion of FEC in the electrolyte is 5%.

[0272] 3. Isolation film

[0273] Polyethylene film is used as the isolation membrane.

[0274] 4. Preparation of button cells

[0275] The negative electrode sheet is used as the working electrode and the metallic lithium is used as the counter electrode. The negative electrode sheet, the isolation membrane and the metallic lithium are stacked in order so that the isolation membrane is between the working electrode and the counter electrode, and the electrolyte is injected to assemble a button battery.

[0276] At 25°C, discharge to 5 mV at 0.05C constant current, let stand for 10 min, charge to 2.0V at 0.1C, and obtain the first discharge capacity and first charge capacity, then the first coulomb efficiency = first discharge capacity / first charge capacity × 100%. Table 5 is obtained.

[0277] Table 5 Performance list (I)

[0278]

[0279]

[0280] 2. Preparation of secondary batteries:

[0281] 5. Negative electrode

[0282] The silicon-carbon composite material prepared above, the conductive agent carbon nanotube and SP mixture, the binder styrene-butadiene rubber, and the thickener sodium carboxymethyl cellulose were fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 95.0:1:5:1.5:2.0 to form a negative electrode slurry. The negative electrode slurry was coated on both surfaces of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet was obtained.

[0283] 6. Positive electrode

[0284] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM 811 ) was mixed with conductive carbon black and polyvinylidene fluoride in a weight ratio of 97.5:1.2:1.3, and an appropriate amount of solvent NMP was added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained.

[0285] 7. Electrolyte:

[0286] A mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) was used as an organic solvent, wherein the volume ratio of EC, EMC and DEC was 20%:20%:60%. In an argon atmosphere glove box with a water content of <10 ppm, a fully dried lithium salt (LiPF6 ) is dissolved in the above organic solvent, and an additive, fluoroethylene carbonate (FEC), is added to obtain an electrolyte. In the electrolyte, LiPF 6 The concentration is 1 mol / L, and the mass proportion of FEC in the electrolyte is 5%.

[0287] 8. Isolation film

[0288] Polyethylene film is used as the isolation membrane.

[0289] 9. Preparation of Secondary Batteries

[0290] Place the separator and the positive and negative electrodes prepared above in order, so that the separator is between the positive and negative electrodes to play an isolating role, and then wind to obtain an electrode assembly; place the electrode assembly in an outer package, dry it, inject the above-prepared electrolyte, and obtain a soft-pack secondary battery after vacuum packaging, standing, formation, capacity and other processes. The size of the secondary battery is 135mm×72mm×60mm, and the capacity is 4.65Ah.

[0291] (1) At 25°C, the number of cycles corresponding to the discharge capacity of the secondary battery decaying to 80% of the initial discharge capacity:

[0292] At 25°C, the prepared secondary battery (full battery) is charged to 4.25V at 0.5C, and then discharged to 2.5V at 1C. This is a cycle charge and discharge process, and the discharge capacity at this time is recorded as the initial discharge capacity. The secondary battery is further subjected to the cycle charge and discharge test according to the above method, and the discharge capacity after each cycle is recorded until the discharge capacity of the secondary battery decays to 80% of the initial discharge capacity, and the number of cycles at this time is recorded.

[0293] (2) Electrode cyclic expansion performance test at 45°C:

[0294] The thickness of the negative electrode of the battery after the cold pressing process is recorded as h0. According to the above-mentioned test method for the cycle performance of the secondary battery at 45°C, the secondary battery is cycled for 300cls, charged at a constant current of 1C to a voltage of 4.25V, and then charged at a constant voltage of 4.25V to a current of less than or equal to 0.05mA, and then left to stand for 5min. The cycled battery cell is disassembled in a drying room, and the thickness of the negative electrode after 300cls of cycling is recorded as h300, and the expansion rate of the secondary battery at 45°C for 300cls of cycling is Δh300.

[0295] Δh300(%)=(h300-h0) / h0*100%.

[0296] The test results are shown in Table 6.

[0297] Table 6 Performance list (II)

[0298] - Number of cycles (circles) Cyclic expansion (%) Example 1 1325 38.5% Example 2 1300 42.3% Example 3 1310 41.5% Example 4 1300 43.2% Example 5 1315 42% Example 6 1318 41.8% Example 7 1320 39.0% Example 8 1322 38.5% Example 9 1321 38.8% Example 10 1320 39.2% Embodiment 11 1320 39.0% Comparative Example 1 1265 42% Comparative Example 2 1150 45.8% Comparative Example 3 980 50.4%

[0299] Combined with the above list, it can be seen that in the silicon-carbon material provided by this application, the silicon grains are mainly formed in the micropores of the porous carbon material to facilitate the control of the specific content, and most of the reserved mesopores are mainly used as volume space to buffer the expansion of the silicon material. The carbon coating layer as an outer shell layer can reduce the probability of silicon grains contacting with the outside air and then being oxidized on the one hand, and on the other hand, it can reduce the probability of silicon grains contacting and reacting with the electrolyte. Therefore, the silicon-carbon material designed in this application improves the cycle performance of the battery by reducing the cycle expansion while maintaining the relatively high initial efficiency of the material, thereby increasing the number of cycles of the battery.

[0300] In combination with Examples 1 to 11, it can be seen that, generally speaking, the larger the average pore size of the porous carbon material of the present application is within a certain range, the larger the number of its mesopores is within the range. At this time, by controlling certain reaction conditions, the size of the silicon grains in the micropores is relatively larger, and the probability of relatively large silicon grains reacting with electrolytes is reduced. Sufficient mesopores can also reserve some volume space for buffering the expansion of silicon materials, thereby improving the cyclability of the battery by limiting the volume expansion of the silicon material during the process of lithium insertion and extraction.

[0301] In combination with Comparative Example 1, it can be seen that by reducing the micropowder particles attached to the surface of the carbon particles of the porous carbon material in the preparation process, the volume distribution particle size concentration of the carbon particles is improved, which is also beneficial to increase the number of battery cycles.

[0302] Combining Comparative Examples 2 and 3, it can be seen that the porous structure of the present application is affected by the preparation process, and the porous structure is highly compatible with the silicon grain size, both of which have a great influence on the first efficiency and cyclability of the battery.

[0303] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A porous carbon material, characterized in that: The porous carbon material comprises carbon particles, the carbon particles have a porous structure, and the porous carbon material satisfies the following conditions: (1.1) The porous structure comprises mesopores and micropores, and the number of the mesopores is not less than the number of the micropores; (1.2) The volume distribution particle size of the carbon particles satisfies: Dv1 ≥ 0.5 μm; (1.3) The specific surface area of ​​the porous carbon material is 1400 m 2 / g~1800m 2 / g.

2. The porous carbon material according to claim 1, characterized in that: The volume distribution particle size of the carbon particles satisfies: Dv1 is 0.5 μm to 1.0 μm.

3. The porous carbon material according to claim 1, characterized in that: The volume distribution particle size DV of the carbon particles 50 、DV 90 With DV 10 Satisfy the following: DV 50 3μm~20μm;DV 90 ≤35μm;DV 10 >1.5μm.

4. The porous carbon material according to claim 3, characterized in that: The volume distribution particle size DV of the carbon particles 50 5μm~19μm.

5. The porous carbon material according to claim 1, characterized in that: The specific surface area of ​​the porous carbon material is 1450 m 2 / g~1750m 2 / g.

6. The porous carbon material according to any one of claims 1 to 5, characterized in that: The porous structure meets the following conditions: (2.1) The number of the mesopores accounts for more than 50% of the number of the porous structure; (2.2) The number of the micropores is less than 50% of the number of the porous structure; (2.3) The average pore size of the porous structure is 1.0 nm to 10 nm.

7. The porous carbon material according to claim 6, characterized in that: The porous structure satisfies at least one of the following: (3.1) The number of the mesopores accounts for 50% to 70% of the number of the porous structure; (3.2) The number of the micropores accounts for 30% to 50% of the number of the porous structure; (3.3) The average pore size of the porous structure is 2.0 nm to 8.0 nm.

8. The porous carbon material according to any one of claims 1 to 7, characterized in that: The pore volume of the porous carbon material is 0.8 cm 3 / g~1.4cm 3 / g.

9. A silicon-carbon material, characterized in that: The porous carbon material comprises the porous carbon material according to any one of claims 1 to 8, further comprising silicon grains and a carbon coating layer, wherein the silicon grains are formed in the porous structure; and the carbon coating layer is located outside the porous carbon material.

10. The silicon-carbon material according to claim 9, characterized in that: Based on the total mass of the silicon-carbon material, the mass percentage content of silicon element in the silicon-carbon material is 30% to 40%.

11. The silicon-carbon material according to any one of claims 9 to 10, characterized in that: The silicon grains are formed in the micropores of the porous structure; The grain size of the silicon grains is ≤8.0 nm.

12. The silicon-carbon material according to claim 11, characterized in that: The grain size of the silicon grains is 5.0 nm to 8.0 nm.

13. The silicon-carbon material according to any one of claims 9 to 12, characterized in that: The silicon-carbon material comprises silicon-carbon particles, and the silicon-carbon particles meet the following conditions: (4.1) Volume distribution particle size DV of the silicon-carbon particles 50 、DV 90 With DV 10 Satisfy: (DV 90 -DV 10 ) / DV 50 1.0~3.0; (4.2) The tap density of the silicon carbon particles is 0.85 g / cm 3 ~1.1g / cm 3 ; (4.3) The specific surface area of ​​the silicon-carbon particles is 2.0 m 2 / g~8.0m 2 / g.

14. The silicon-carbon material according to claim 13, characterized in that: The silicon-carbon particles satisfy at least one of the following requirements: (5.1) Volume distribution particle size DV of the silicon-carbon particles 50 、DV 90 With DV 10 Meets: DV 50 3μm~30μm;DV 90 ≤60μm; DV 10 >2.0μm; (5.2) The tap density of the silicon carbon particles is 0.85 g / cm 3 ~1.0g / cm 3 ; (5.3) The specific surface area of ​​the silicon-carbon particles is 3.0 m 2 / g~6.0m 2 / g.

15. The silicon-carbon material according to any one of claims 9 to 14, characterized in that: The pore volume of the silicon carbon particles is 0.01 cm 3 / g~0.05cm 3 / g.

16. The silicon-carbon material according to any one of claims 9 to 15, characterized in that: The properties of the silicon-carbon material satisfy at least one of the following: (6.1) The silicon-carbon material is used as the positive electrode active material and metallic lithium is used as the counter electrode to assemble a button-type battery. At 25°C, the battery is discharged to 5 mV using a constant current of 0.05C, left to stand for 10 min, and charged to 2.0 V using 0.1C. The initial coulombic efficiency is ≥90%; (6.2) The powder resistivity of the silicon-carbon material under a pressure of 16 MPa is ≤3 Ω·cm.

17. A method for preparing the silicon-carbon material according to any one of claims 9 to 16, characterized in that: These include: preparing porous carbon materials; A silicon source is introduced into the porous carbon material, and generated silicon grains are formed in the porous structure of the porous carbon material; Stop introducing the silicon source gas, and selectively introduce a carbon source to generate a silicon-carbon material including a carbon coating layer.

18. The preparation method according to claim 17, characterized in that: The preparation of the porous carbon material comprises: The carbon material precursor is subjected to high temperature treatment, mixed with an excess of strong alkali and continued to be heated to obtain an alkali-activated material, excess strong alkali in the alkali-activated material is removed, the material is crushed, and small-sized particles are removed to obtain carbon particles.

19. The preparation method according to claim 18, characterized in that: The material obtained by mixing with an excess of strong alkali and heating continuously to obtain alkali-activated material comprises: The carbon material after high temperature treatment is mixed with a strong base, heated to 900°C to 1000°C in an inert atmosphere, and kept warm for 1h to 12h; The mass ratio of the carbon material after high temperature treatment to the strong base is 1:(7-10); The strong base includes any one of sodium hydroxide and potassium hydroxide.

20. The preparation method according to any one of claims 18 to 19, characterized in that: The method for removing excess strong alkali in the material after alkali activation comprises: The alkali-activated material is immersed in an acidic solution for full reaction, taken out, washed with water and then dried; The acidic solution includes any one of a hydrochloric acid solution, a sulfuric acid solution, and a phosphoric acid solution.

21. A secondary battery, comprising a negative electrode plate, characterized in that: The negative electrode plate comprises the porous carbon material according to any one of claims 1 to 8, the silicon-carbon material according to any one of claims 9 to 16, or the silicon-carbon material prepared by the preparation method according to any one of claims 17 to 20.

22. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 21.

Citation Information

Patent Citations

  • Carbonaceous material for negative electrode of nonaqueous-electrolyte secondary battery, process for producing same, and negative electrode and nonaqueous-electrolyte secondary battery obtained using said carbonaceous material

    CN104412426A

  • Mesopore and micropore carbon material, and preparation method and application thereof

    CN106865546A

  • Coal-based porous carbon, preparation method and application thereof, and lithium ion capacitor

    CN112017870A

  • Electroactive materials for metal-ion batteries

    CN113169308A

  • Preparation method of silicon-carbon negative electrode material

    CN116314791A

Cited By

  • Silicon-carbon negative electrode material utilizing atomic layer deposition and preparation method of silicon-carbon negative electrode material

    CN120432511A

  • Silicon-carbon negative electrode material and preparation method thereof, negative electrode plate and electrochemical device

    CN121460535A

  • Battery cell, silicon-carbon composite material and preparation method, battery device, and electric device

    WO2026036694A1